Implementasi Kebijakan Pembangunan Pariwisata di Kawasan UNESCO Desa Jatiluwih Kabupaten Tabanan - Theresia, Winda Ayu; Noak, Piers Andreas; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 2 No 1 (2023): Jurnal Ilmu Politik, 2023)
This study wants to examine related to tourism development that occurred in Jatiluwih Village. This development is carried out to support the growth of tourism in Jatiluwih Village, to provide adequate facilities for visitors. However, since Jatiluwih Village is designated as a World Cultural Heritage (WBD), development in Jatiluwih Village continues to increase every year, this tourism development certainly reaps cons from various levels of society, especially farmers, because it affects water conditions and tourists who come actually damage the rice fields which it hurts farmers. Because of this adverse condition, it is a question of how the local government understands the contents of the UNESCO agreement, because with this title, the rice fields in Jatiluwih Village should be protected and preserved but in fact the opposite is happening, development continues and more tourists arrive. This tourism development that occurs can also be seen from the perspective of the community who actually supports the increase in tourism so that their income can increase which is useful for their welfare. So, this study uses the theory of Heritage to see the purpose of this tourism development and see the direction of tourism development that occurs in Jatiluwih Village and the responses and thoughts of the community. Keywords          : Tourism, Development, UNESCO, World Heritage